Bioreduction mechanisms of high-concentration hexavalent chromium using sulfur salts by photosynthetic bacteria. (January 2023) - Su, Yan-Qiu; Min, Shuang-Nan; Jian, Xin-Yi; Guo, Yuan-Cheng; He, Shu-Hao; Huang, Chun-Yi; Zhang, Zheng; Yuan, Shu; Chen, Yang-Er
Abstract: Eliminating "sulfur starvation" caused by competition for sulfate transporters between chromate and sulfate is crucial to enhance the content of sulfur-containing compounds and improve the tolerance and reduction capability of Cr(VI) in bacteria. In this study, the effects of sulfur salts on the Cr(VI) bioremediation and the possible mechanism were investigated in Rhodobacter sphaeroides SC01 by cell imaging, spectroscopy, and biochemical measurements. The results showed that, when the concentration of metabisulfite was 2.0 g L −1, and the initial OD600 was 0.33, the reduction rate of R. sphaeroides SC01 reached up to 91.3% for 500 mg L −1 Cr(VI) exposure at 96 h. Moreover, thiosulfate and sulfite also markedly increased the concentration of reduced Cr(VI) in R. sphaeroides SC01. Furthermore, the characterization results revealed that –OH, –CONH, –COOH, –SO3, -PO3, and -S-S- played a major role in the adsorption of Cr, and Cr(III) reduced by bacteria was bioprecipitated in the production of Cr2 P3 S9 and CrPS4 . In addition, R. sphaeroids SC01 combined with metabisulfite significantly increased the activity of glutathione peroxidase and the content of glutathione (GSH) and total sulfhydryl while decreasing reactive oxygen species (ROS) accumulation and cell death induced by Cr(VI) toxic. Overall, the results of this research revealed a highly efficient and reliable strategy for Cr(VI) removal by photosynthetic bacteria combined with sulfur salts in high-concentration Cr(VI)-contaminated wastewater. Graphical abstract: Image 1 Highlights: There was an obvious synergistic effects of Na2 S2 O5 with SC01. Cr(VI) reduction rate adding Na2 S2 O5 was 42.50% higher than that of the control. Cr(III) existed as Cr2 P3 S9 and CrPS4 in SC01 with three sulfurs. Na2 S2 O5 could eliminate ROS by promoting GPX enzyme activity and GSH content, and improve the Cr(VI) reduction.